Predator or prey? Parasitic enterprises in economic development - Halvor Mehlum; Karl Moene; Ragnar Torvik (University of Oslo, Department of Economics, 2000)
In many developing and transition economies Mafia-like activities are rampant. Extortion and other forms of predation lower profitability in private businesses and distort investment incentives. Incorporated in a model of industrialization, bimodal club convergence may result. Economies may get stuck in a Predators' Club characterized by a vicious circle of poverty and predation. Societies with a low flow of new entrepreneurs are especially vulnerable to predation and never get out of this club. Poor societies with high flow of new entrepreneurs, however, may grow out of the trap and join the rich Producers' Club.
Keywords: O1; O4; 330; Poverty traps; Club convergence; Organized crime; Organisierte Kriminalität; Armut; Entwicklung; Theorie; Ökonomische Sicherheit